The Design and Evaluation of Camshaft Used in Multi Cylinder Engine (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The camshaft is driven by the crankshaft through timing gears cams are made as integral parts of the camshaft and are designed in such a way to open and close the valves at the correct timing and to keep them open for the necessary duration. A common example is the camshaft of an automobile, which takes the rotary motion of the engine and translates it into the reciprocating motion necessary to operate the intake and exhaust valves of the cylinders. In this work, a camshaft is designed for multi cylinder engine and 3D-model of the camshaft is created using modeling software CATIA. The modeled in CATIA is imported in to ANSYS. After completing the element properties, meshing and constraints the loads are applied on camshaft for three different materials namely SS 316, C55 Mn15, NiCrVMo alloy steel, and EN24T 5. Malleable cast iron to determine the displacement, equivalent stress of the cam shaft.